Higher Education as Soft Power Potential of Russia - M. M. Lebedeva; J. Fort (Vestnik MGIMO-Universiteta, 2009)
Referring to Joseph Nye’s concept of «soft power» the authors examine training of national cadres for other countries as a factor of «soft power» of the Soviet Union and Russia. They note that before the collapse of the USSR 10.8 % of all international students studying abroad did it in the USSR. Almost 80 % of them were from Asia, Africa and Latin America. There was a significant fall in international education in Russia after the collapse of the USSR. At the same time the USA has secured the leading role in international education. International education is becoming a visible area for competition between states. In the 2000s Russia focuses on higher education again. Education has been declared a «national priority». Russia joined the Bologna process and by the year 2020 the financing of education is to reach the level of 7 % of GDP. Russia is battling to improve its image abroad and actively develops its higher education supply for foreign students and is promoting its role as the main educational center for CIS countries. In reality international education is mostly a potential for Russia as no clear program or structure to develop international education exists in the country.